Base-level cycles and episodic coal accumulation - Case study of Dngsheng coalfield in Ordos basin - Yang, Ren-Chao; Han, Zuo-Zhen; Li, Zeng-Xue; Fan, Ai-Ping (Journal of China University of Mining and Technology, 2006)
The advantage of high-resolution sequence stratigraphy, which takes base-levels as reference, is that it can be applied to continental depositional basins controlled by multiple factors and can effectively improve the accuracy and resolution of sequential stratigraphic analysis. Moreover, the principles of base-level cycles are also suitable for analyzing sequential stratigraphy in continental coal-bearing basins because of their accuracy in forecasting distribution of coal measures. By taking the Dongsheng coalfield in the Ordos basin as an example, the extensive application of base-level cycles in exploration and exploitation of coal is analyzed. The result shows that the Yan'an formation in the Dongsheng area is a long-term base-level cycle which is bordered by nonconformities and made up of five mid-term cycles and 13 short-term cycles. The long-term cycle and the mid-term cycles are obvious in comparison with a transverse profile. The episodic coal accumulation in the Mesozoic Ordos basin means that the deposition of primary matter (peat bogs) of coalification is discontinuous, periodical and cyclical in the evolution of the basin. The episodic accumulation of coal measures in the Yan'an stage is controlled by ascending-descending changes of a long-term cycle and middle-term cycles. Coal measures formed during the early and late periods of the long-term cycle are characterized by multiple layers, big cumulative thickness and poor continuity. Coal measures formed in the mid-term of the long cycle are dominated by good continuity, fewer layers and a small additive thickness, which is favorable for the accumulation of thick and continuous coal measures in the transition stage of mid term base-level cycles.